Legal Protection of Land Rights in the Settlement of Double Certificate Disputes Through Supreme Court Decisions (Study of Decision No. 212K/PDT/2020) - Fitri Camelia Ananda; Yenny Febrianti; Eka Ardianto (Civiliza Publishing, 2026)
Dual land certificates represent a systemic problem in Indonesian land administration that creates legal uncertainty and prolonged ownership conflicts. This study aims to analyze the legal protection provided by the Supreme Court through Decision No. 212K/Pdt/2020 in resolving dual certificate disputes, as well as to identify implementation obstacles and countermeasures. The research employs a normative juridical approach combined with an empirical approach through decision analysis, statutory review, and interviews with Notaries/PPAT as land practitioners. Findings indicate that the cassation decision successfully restored substantive legal certainty by prioritizing good faith, chronology of rights acquisition, and physical possession as the basis for determining legitimate Right of Ownership under Articles 20–27 of the Basic Agrarian Law (UUPA). However, the effectiveness of legal protection remains hindered by weak coordination between judicial institutions and the National Land Agency (BPN), protracted verification bureaucracy, and the potential misuse of criminal instruments to delay civil execution. The study recommends establishing standardized court-BPN cooperation protocols, accelerating the transition to electronic land registration, simplifying post-final decision certificate revocation procedures, and applying the ultimum remedium principle in criminal reporting for purely civil land disputes. Thus, legal protection must not end with normative victory but must materialize as administrative certainty genuinely enjoyed by legitimate rights holders.